KARAKTERISTIK FISIK BATA MERAH DAN KAITANNYA DENGAN ANALISA HARGA SATUAN PEKERJAAN - Suhendra Suhendra; Elvira Handayani; Mirza Revita (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
Red bricks used as building walls/ Masonry in the city of Jambi in general has not been in accordance with the standards set.Research on the physical characteristics and suitability of the volume of work the Unit Price Analysis Work (AHSP 2013) has been done to the red brick produced in the village Pijoan and the village Setiti.Laboratory examination showed the red brick from the village Pijoan and village Setiti not meet the requirements in terms of compressive strength and dimensional standards used in AHSP 2013. The Large enough absorption of water implied that before using the red bricks must be soaked first so that the existing water in mortar is not reduced because of the red brick absorbed. Differences with standard dimensions cause additional material of Portland Cement and Sand Put on a red brick wall mounting.Key words:   Bata merah, Karakteristik fisik, Analisa Harga Satuan Pekerjaan